Dynamical behavior of quantum-dot laser - M.O. Oleiwi (مجلة علوم ذي قار, 2019)
In this work we have investigated the dynamical properties of InAs/InGaAs laser emitting 1.3? m pumped by injection current density of fast rise and falling times with a duration of 5ns . In (capture) and out (escape) scattering rates of electrons and holes are studied against temperature, injection current density, Auger coefficient .Scattering times are studied against carrier reservoir loss coefficient , injection current density and temperature. Temporal behavior of photons density against injection current density is given too.